Strategies to Support the Interests of Aboriginal and Torres Strait Islander Peoples in the Commercial Development of Gourmet Bush Food Products. Issue 1 (3rd March 2016) - Lingard, Kylie; Martin, Paul
Abstract: Indigenous groups and individuals may have different needs and aspirations in relation to their local plant foods ("bush foods"). Interests may reflect totemic relationships, customary rights and duties, social positions, political and economic motivations, and personal capacities. This article uses a systems method to identify strategies to support the diverse interests of Australia's Aboriginal and Torres Strait Islander peoples in the commercial development of gourmet bush food products. The aim is to identify possibilities for further consideration by Aboriginal and Torres Strait Islander peoples.